Boaters Alert! - Charles Jacoby; Nanette Holland; Gail Stout (EDIS, 2006)
FA130, a 2-page full-color fact sheet by Charles Jacoby, Nanette Holland and Gail Stout, helps boaters identify some known and potential introduced species in Florida, provides a contact for reporting sightings of these species, and suggests steps that boaters can take to reduce the spread of introduced species. Published by the UF Department of Fisheries and Aquatic Sciences, December 2006.